Changes in tooth size of Otaria byronia: an indicator of density-dependent effects? - Sosa Drouville,Ailin; Heredia,Federico; Coscarella,Mariano A.; Crespo,Enrique; Grandi,María Florencia (PeerJ, 2025)
Teeth provide valuable information about an individual’s life cycle and serve as a powerful tool for visualizing population-level changes associated with density-dependent processes. In pinnipeds, teeth are used to estimate the age of individuals based on the count of growth layer groups (GLG) in the dentine. In this study, we analyzed changes in tooth size and GLG widths in the canines of Otaria byronia throughout the past 100 years, linking these to fluctuations in population abundance. A total of 76 male individuals from Patagonia were analyzed, classified into two periods: harvest and postharvest. The length and diameter of each tooth were measured prior to sagittal sectioning. Only for the postharvest period body length was recorded. Longitudinal sections of the upper canine were prepared, age was determined and the width of each GLG was measured in the resulting half-tooth. Results indicated a positive correlation (F = 62.90; p < 0.001; n = 50; r2 = 0.59) between body length and tooth length in postharvest individuals, suggesting that tooth growth is a reliable indicator of body growth. Individuals from the harvest period had narrower GLGs (t = 3.75; p < 0.001) and smaller tooth size (t = 3.48; p < 0.001) compared to those from the postharvest period. These results indicate that somatic growth of individuals may vary with population numbers and resources available. Also, hard structures like teeth are excellent tools for visualizing density-dependence effects.
Keywords: Density-dependence; Pinnipeds; Teeth; South American sea lion; Otaria byronia